Experimental Data and Thermodynamics Modeling (eNRTL and mUNIFAC) of the (Cyclohexane + Benzene + N,N-Dimethylformamide + Sodium Thiocyanate) Systems - Lenhare, Stephanie; de Souza, Beatriz Fernanda Bonfim; Miyasaki, Fernanda Viana [UNESP]; Zuber, André; Arce, Pedro; Ferreira-Pinto, Leandro [UNESP]; Beneti, Stéphani Caroline; Cardozo-Filho, Lúcio; Zanette, Andréia Fátima [UNESP] (MDPI, 2025)
This study investigates the liquid–liquid equilibrium (LLE) of a cyclohexane (1) + benzene (2) + [N,N-dimethylformamide + sodium thiocyanate] (3) system. Experimental tie-line data were obtained at 298.15 K and 318.15 K under atmospheric pressure (~101 kPa, Maringá, Paraná, Brazil) with varying sodium thiocyanate (NaSCN) concentrations in N, N-dimethylformamide (DMF) (3, 5, 8, and 16 wt%). The results contribute to determining the optimal operating conditions for the liquid–liquid extraction of cyclohexane/benzene mixtures. The Hand and Othmer–Tobias correlations confirm the consistency and accuracy of the experimental data. Furthermore, eNRTL and modified UNIFAC models were employed to correlate the experimental LLE data, achieving a root-mean-square deviation of less than 0.91%. The selectivity and distribution coefficients indicate a high efficiency of benzene distribution into the extract phase, suggesting a low solvent/feed ratio and fewer separation stages required for cyclohexane and benzene separation.
Keywords: benzene; cyclohexane; eNRTL; liquid–liquid equilibrium; mUNIFAC; NaSCN